Integrative Structural Biology with Hybrid Methods (Advances in Experimental Medicine and Biology, 2018)
This book presents a new emerging concept of "Integrative Structural Biology". It covers current trends of the molecular and cellular structural biology, providing new methods to observe, validate, and keep the structural models of the large cellular machines with recent scientific results. Structures of very large macromolecular machines in cells are being determined by combining observations from complementary experimental methods. Thus, this volume presents the each methods such as X-ray crystallography, NMR spectroscopy, 3DEM, small-angle scattering (SAS), FRET, crosslinking, and enables the readers to understand the hybrid methods. This book discusses how those integrative models should be represented, validated and archived. A unique highlight of this book is discussion of the data validation and archive, which are big problems in this filed along with the progress of this field. The researchers in biology will be interested in this book as a guide book for learning the current structure biology, but also those in structure biology may use this book as a comprehensive reference to cover broad topics.